Plant trait-mediated drag forces on seedlings of four tidal marsh pioneer species - Steinigeweg, Charlotte S.; Löbel, Swantje; Schröder, Boris; Schoutens, Ken; Reents, Svenja; Evans, Ben R.; Temmerman, Stijn; Bouma, Tjeerd J.; Möller, Iris; Paul, Maike (Frontiers in Marine Science, 2023)
Salt marshes play an important role in coastal protection by reducing the impact of waves and shoreline erosion risks. While mature vegetation is responsible for the persistence and stability of marsh ecosystems, seedling survival of pioneer species is especially crucial for marsh propagation. Marsh seedlings, however, may be threatened by climate change induced increased coastal storm surge intensity and accompanying (extreme) wave conditions, imposing stronger drag forces on marsh seedlings. We test the hypothesis that drag forces experienced by seedlings increase with horizontal orbital velocity (Uw) in a species-specific manner, and that the drag forces experienced are individual-plant trait-mediated. To test our hypotheses, seedlings of four contrasting pioneer marsh species (Bolboschoenus maritimus, Schoenoplectus tabernaemontani, Spartina anglica, and Puccinellia maritima) were exposed to storm wave conditions in a flume, where Uw and experienced drag forces were measured. Linear mixed effect models demonstrated that seedling’s susceptibility to storm wave conditions is at least partly mediated by individual plant traits. Drag forces experienced by seedlings tended to increase with Uw, and with stem length and diameter. The interplay of both traits was complex, with increasing stem length being the most important trait accounting for increases in drag forces experienced at low to moderate Uw, while the stem diameter became more important with increasing Uw. Furthermore, experienced drag forces appeared to be affected by species-specific traits such as rigidity and leaf growth, being highest for Bolboschoenus maritimus and lowest for Puccinellia maritima. Our results provide important mechanistic insights into the drivers of tidal marsh seedling vulnerability to storm wave conditions due to experienced drag, both based on the traits of individual plants and species-specific ones. This type of knowledge is of key importance when modelling saltmarsh establishment and resilience under climate change.